Usability Perspective of an Authoring Solution to Assist Pedagogical Decision-Making - Paiva, Ranilson; Bittencourt, Ig Ibert; Vinicius, André; Amorim, Sérgio; Lemos, Wansel; Dermeval, Diego; Isotani, Seiji (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2017)
There is a quest to provide education from anywhere, at any time and for anyone, using digital information and communication technologies, but there is no equivalent increase in support for the instructors responsible for maintaining such courses, evidenced by the large number of dropouts and failures. We propose an authoring solution to guide pedagogical decision-making in on-line learning environments to help instructors (1) to discover pedagogical situations occurring in their courses; (2) understand these situation; (3) make decisions to address them; (4) monitor and evaluate the impact from decisions made. However, instructors do not master these abilities, nor is it practical/appropriate to ask them to do so. We developed a proof-of-concept version of an authoring solution, named T-Partner, that guides instructors through these 4 steps. We conducted an experiment to evaluate whether it is perceived as useful and easy to use. The results show that its usefulness and ease of use were positively perceived by the instructors.